PENGARUH MOTIVASI, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Jahroni Jahroni; Didit Darmawan (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
Employee performance appraisal is important to ensure that the company's organizational operations are running according to the main plan and strategic policies. Observation of employee performance needs to be carried out continuously to find out any disturbances and drivers for the formation of performance. This study intends to observe the role of work motivation, discipline and work environment in shaping employee performance. The study was conducted on 142 employees. With the regression technique and SPSS found several things. Motivation, discipline and the workplace environment are proven to simultaneously have a role in the formation of employee performance. Likewise with the role partially. Work environment variables become variables that play a dominant role.